TRANSLATION STRATEGIES USED BY EFL LEARNERS IN TRANSLATING NARRATIVE TEXT - Gustin Hidayanti; Sabarun Sabarun; Hesty Widiastuty (IKIP Siliwangi, 2023)
This research aimed to explain strategies, and most dominant strategies in the translating process used by students of the Institut Agama Islam Negeri Palangka Raya English Language Study Program for interpreting narrative texts. Translation is a means of communication and translation strategy is a way to improve the ability to translate a text. This research uses a descriptive qualitative approach with personal data sources. Data was acquired through the use of questionnaires and interviews. The authors' analysis was based on the outcomes of a translation challenge given by 55 students. The finding revealed that the students employed all seven translation strategies from Vinay and Darbelnet when translating the narrative text. The three most regularly utilized translation strategies are borrowing (78%), Calque (61%), and Modulation (56%). This research is expected to provide insight into language training, particularly translation linked to translation methodologies utilised to translate. The correct application of the translation method during the translation process will result in accurate translation. Results of this study emphasise the need of offering tailored translation strategies teaching to EFL students.